Microbiome and Autoimmune Uveitis - Horai, Reiko; Caspi, Rachel R. (Frontiers in Immunology, 2019)
Commensal microbes affect all aspects of immune development and homeostasis in health and disease. Increasing evidence points to the notion that the gut commensals impact not only intestinal diseases but also diseases in tissues distant from the gut. Autoimmune or non-infectious uveitis is a sight-threatening intraocular inflammation that affects the neuroretina. It is strongly T cell driven, but the precise causative mechanisms are not fully understood. We and others observed that depletion of gut microbiota in animal models of uveitis attenuated disease. Using a spontaneous model of the disease, we questioned how retina-specific uveitogenic T cells are primed when their cognate antigens are sequestered within the immune privileged eye. The data suggested that gut commensals provide a signal directly through the retina-specific T cell receptor and cause these autoreactive T cells to trigger uveitis. This activation of retina-specific T cells in the gut appears to be independent of the endogenous retinal antigen. Rather, the findings point to the notion that gut microbiota may mimic retinal antigen(s), however, the actual mimic has not yet been identified. Microbiota may also serve as an “adjuvant” providing innate signals that amplify and direct the host immune response for development of uveitis. In contrast, spontaneous uveitis that develops in AIRE-/- mice appears to be independent of gut microbiota. To date, available data on human microbiota in association with uveitis are very limited and causative relationships are difficult to establish. This review will summarize the current knowledge on the role of microbiome in uveitis and its underlying mechanisms, and discuss unresolved questions and issues in an attempt to explore the concept of gut-retina axis.